Effects of different strains Penicillium nalgiovense in the Nalžovy cheese during ripening - Mrázek, Josef; Pachlová, Vendula; Buňka, František; Černíková, Michaela; Dráb, Vladimír; Bejblová, Martina; Staněk, Karel; Buňková, Leona (Journal of the Science of Food and Agriculture, 2016)
BACKGROUND: The present study examined the influence of eight selected strains of Penicillium nalgiovense as secondary culture on the ripening of soft mould cheese. Ion-exchange chromatography, SDS-PAGE and sensory analysis were used for comparison of P. nalgiovense with common secondary mould culture (Penicillium camemberti). RESULTS: Proteolytic activity was more intensive in the case of the strains of P. nalgiovense in comparison with the control strains of P. camemberti. Some differences in the proportion and amount of free amino acids were observed between the strains of P. nalgiovense during ripening. Lower proteolytic activity of P. nalgiovense was more desirable for sensory properties of cheese, especially in case sample N2. CONCLUSION: This study provides information on the usability of selected strains of P. nalgiovense that could support the development of sensory properties of mould-ripened soft cheese. The cheese with the culture N2 had the best flavour after 35 days of storage. Moreover, this strain showed the lowest bitterness in comparison with the other used P. nalgiovense cultures. The intensity of bitterness of sample N2 was comparable to that of the control sample with P. camemberti. © 2015 Society of Chemical Industry.
Keywords: sýr; Cheese; Penicillium; Food Microbiology; potravinářská mikrobiologie